The Formation of Nationalism-Religious Country in Malaysia - Ahmad Farid Abd Jalal; Rahimin Affandi Abdul Rahim; Ahnaf Wafi bin Alias; Siti Maimunah Binti Kahal (Parahyangan Catholic University, 2022)
After independence, efforts to reconstruct the history of ancient Malaysia recorded by colonial scholars have been made. However, there are still poor explanations. Therefore, the following studies are the study of the history of the Malay community in a new interpretation. The methods used in this study are phenomenological. With this method it was found that the process of independence of Malaya in 1957 did not take place in the short run by the British and its elite, but it took a long time and made little sacrifice. It started in the form of awareness by scholars of Malay nationalism itself which unfortunately has been forgotten or closed their role by chroniclers.